2019
DOI: 10.4236/ojpm.2019.95005
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cord Care Practices among Mothers in Abakaliki, Ebonyi State, South East, Nigeria

Abstract: Introduction: Unhygienic cord-care practices are major public health concern because of the associated gross neonatal and infant morbidity and mortality. Various factors have been linked to these practices. This study aims to identify the determinants of cord care practices among mothers in Abakaliki, Ebonyi State, South East, Nigeria. Methods: A cross sectional questionnaire based study involving women attending antenatal clinics and those who brought their babies to the immunization clinics of Federal Teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
4
10
0
Order By: Relevance
“…Our study also revealed that older and multiparous women are more likely to have good cord care practices. This finding is similar to what was found in Eastern Nigeria, where demographic factors like parity, education, and occupation were related to cord care practices [ 39 ]. It is likely that education and experience resulting from the indicated factors put the women in a better position to care for their neonates umbilical cords.…”
Section: Discussionsupporting
confidence: 89%
“…Our study also revealed that older and multiparous women are more likely to have good cord care practices. This finding is similar to what was found in Eastern Nigeria, where demographic factors like parity, education, and occupation were related to cord care practices [ 39 ]. It is likely that education and experience resulting from the indicated factors put the women in a better position to care for their neonates umbilical cords.…”
Section: Discussionsupporting
confidence: 89%
“…On cord care, which are steps applied in the handling of the Austin J Womens Health 9(1): id1063 (2022) -Page -08 Submit your Manuscript | www.austinpublishinggroup.com umbilical cord after delivery, our finding shows that across all the LGAs, seventy nine percent of respondents used methylated spirit for cord care. This finding is close to studies conducted in Jos, Nigeria (73.2%), Abakaliki, Nigeria (82%), Benin, Nigeria (75%) where methylated spirit alone or in combination with other substances were used, Makurdi, Nigeria (70%) where also methylated spirit and methylated spirit plus were used as well as (95.7%) in Primary Health Centers in Ibadan, Nigeria [31][32][33][34][35]. In other studies, in Konduga LGA in Borno, Sokoto and Bauchi, Nigeria, use of methylated spirit was 8.5%, 2.6% and 6.3% respectively in the 2008, 2015 and 2015 respectively [27,36].…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings have been reported by Asiegbu et al, in Nigeria that women who were primipara had good cord care practice compared to those who had many children. [ 7 ] However, this is contrary to the study of Chizoma et al, which reported that the cord care practice improved with the increasing number of children. [ 18 ] These conflicting findings suggest more studies need to be conducted to confirm the role of parity status in cord care practice.…”
Section: Discussionmentioning
confidence: 78%
“…In the study done in Nigeria showed that, maternal level of education, occupation and parity were significant determinants of the care given to the umbilical cord care. [ 7 ] while good knowledge of umbilical cord care was strongly associated with the increasing age, higher education, and marital status. [ 8 ] The study conducted in Tanzania reported that good knowledge of umbilical cord care was determined by having higher level of education and having 3 and more children.…”
Section: Introductionmentioning
confidence: 99%